Self-assembled structure of hydrolyzed sodium hyaluronate and its preparation method and application
By forming a self-assembled structure of hydrolyzed sodium hyaluronate, combining the combination of polyol and acetylated sodium hyaluronate, the problem of small molecule sodium hyaluronate easily turns yellow at high temperatures is solved, and its activity and stability are achieved. Improve and broaden its application scenarios.
Patent Information
- Application Number
- CN202111502112.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-09
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2041-12-09
AI Technical Summary
Small molecule sodium hyaluronate tends to turn yellow under high temperature environments, limiting its application scenarios and ability to exert its characteristics.
By forming a self-assembled structure of hydrolyzed sodium hyaluronate, combining the combination of polyol and acetylated sodium hyaluronate, a self-assembled structure of sodium hyaluronate with higher activity and stability was prepared.
It effectively alleviates the problem of small molecule sodium hyaluronate turning yellow at high temperatures, improves its activity and stability, and broadens its application scenarios in skin care products.
Smart Images

Figure BDA0003402149400000091 
Figure BDA0003402149400000121 
Figure BDA0003402149400000131
Abstract
Description
Technical Field
[0001] The invention belongs to the field of cosmetics, and in particular relates to a self-assembly structure of hydrolyzed sodium hyaluronate and a preparation method and application thereof. Background Art
[0002] Sodium hyaluronate (HA), also known as sodium hyaluronate, is a natural high molecular linear mucopolysaccharide composed of D-glucuronic acid and N-acetylglucosamine as disaccharide units repeatedly connected. It is widely present in animal tissues and body fluids, such as joint fluid, vitreous body, umbilical cord, skin, etc. Sodium hyaluronate has good viscoelasticity and excellent water retention due to its unique structure, and has important physiological functions and biological effects, and has good tissue compatibility and non-immunogenicity, so it has a wide range of applications. At present, the application fields of sodium hyaluronate in my country are mainly concentrated in the pharmaceutical, clinical diagnosis and treatment and cosmetics industries, accounting for more than 98% of the total amount. In the fields of medicine and clinical diagnosis and treatment, it is widely used in various ophthalmic surgeries, such as lens implantation, corneal transplantation and anti-glaucoma surgery, and can also be used to treat arthritis and accelerate wound healing; and using it in cosmetics can play a unique role in protecting the skin, keeping the skin moisturized, smooth, delicate, tender and elastic, and has the effects of anti-wrinkle, anti-wrinkle, beauty care and restoring the physiological functions of the skin.
[0003] Hyaluronic acid and its salts (HA) are widely present in nature and are important components of human and animal skin, vitreous body, synovial fluid and cartilage tissue. They are composed of repeated connections of disaccharide units of (1-β-4) D-glucuronic acid (1-β-3) N-acetylglucosamine and are a chain polyanionic macromolecular mucopolysaccharide. They are widely used in the fields of medicine, daily chemicals and food. HA has good biocompatibility and few side effects. Studies have shown that the biological activity of HA has obvious M r (Relative molecular weight) dependence.
[0004] According to literature research, the biological activity of sodium hyaluronate is related to the size of the molecular weight. The smaller the molecular weight, the smaller the degree of polymerization, and the higher the biological activity. In the application of cosmetics, sodium hyaluronate with different molecular weights is usually applied to cosmetics with different functions. Large molecular hyaluronic acid can form a breathable film on the surface of the skin, making the skin smooth and moisturized, and can block the invasion of foreign bacteria, dust, and ultraviolet rays to protect the skin from damage; medium molecular hyaluronic acid can tighten the skin and moisturize it for a long time; small molecular hyaluronic acid can penetrate into the dermis, and has the effect of slightly dilating capillaries, increasing blood circulation, improving intermediate metabolism, and promoting skin nutrient absorption. It has a strong wrinkle-removing function, can increase skin elasticity, and delay skin aging. Summary of the invention
[0005] Small molecule hyaluronic acid, such as sodium hyaluronate with a repeating unit of 2-20, is sensitive to temperature. Under high temperature, small molecule hyaluronic acid tends to turn yellow, so there are great restrictions on its operating temperature and storage conditions. In actual application, this not only limits the use of small molecule hyaluronic acid, but also hinders its full performance and the expected effect.
[0006] In view of this, the present invention provides a self-assembled structure containing hydrolyzed sodium hyaluronate, the formation of which can alleviate the yellowing of small molecule sodium hyaluronate, improve the activity of small molecule sodium hyaluronate, and broaden the application scenarios of small molecule sodium hyaluronate.
[0007] Specifically, the present invention adopts the following technical solution
[0008] 1. A self-assembled structure containing hydrolyzed sodium hyaluronate, characterized in that the average particle size is 300 to 2000 nm.
[0009] 2. The self-assembled structure according to item 1, characterized in that in the self-assembled structure, the degree of polymerization of hydrolyzed sodium hyaluronate is 2 to 20.
[0010] 3. The self-assembled structure according to item 1 or 2, characterized in that the self-assembled structure is formed by dispersing hydrolyzed sodium hyaluronate in an aqueous solution of a polyol,
[0011] Preferably, the mass ratio of the hydrolyzed sodium hyaluronate to the polyol is 1:1 to 1:30, and further preferably, the mass ratio of the hydrolyzed sodium hyaluronate to the polyol is 1:5 to 1:20.
[0012] 4. The self-assembled structure according to item 3, characterized in that the polyol is selected from any one or two or more of butanediol, pentanediol, and propylene glycol, preferably one or two of butanediol and pentanediol,
[0013] More preferably, the polyol is a combination of pentanediol and butanediol, and the mass ratio of butanediol to pentanediol is 1:10 to 10:1. More preferably, the mass ratio is 1:5 to 3:1.
[0014] 5. The self-assembled structure according to any one of items 1 to 4, characterized in that the self-assembled structure consists of hydrolyzed sodium hyaluronate.
[0015] 6. The self-assembled structure according to any one of items 1 to 5, characterized in that it also includes acetylated sodium hyaluronate, preferably, the molecular weight of the acetylated sodium hyaluronate is 20 to 100 kDa, and more preferably, the molecular weight is 20 to 50 kDa.
[0016] 7. The self-assembled structure according to item 6, characterized in that the mass ratio of the hydrolyzed sodium hyaluronate to the acetylated sodium hyaluronate is 1:4 to 10:1, preferably 1:2 to 10:1.
[0017] 8. The self-assembled structure according to item 6 or 7, characterized in that the self-assembled structure consists of hydrolyzed sodium hyaluronate and acetylated sodium hyaluronate.
[0018] 9. A method for preparing a self-assembled structure of hydrolyzed sodium hyaluronate, comprising the following steps:
[0019] Weigh hydrolyzed sodium hyaluronate and polyol according to the mass ratio or weigh hydrolyzed sodium hyaluronate, polyol and acetylated sodium hyaluronate according to the mass ratio;
[0020] Dissolve hydrolyzed sodium hyaluronate and polyol in water to form a mixed solution, or dissolve hydrolyzed sodium hyaluronate in water to form phase A, mix acetylated sodium hyaluronate and diol to form phase B, and mix phase A and phase B to form a mixed solution;
[0021] Stirring the mixed solution until it is completely dissolved;
[0022] The completely dissolved solution is allowed to stand and cool;
[0023] Preferably, the mixed solution is heated before being stirred, and more preferably, the heating temperature is 30 to 60° C. and the holding time is 25 to 50 minutes.
[0024] 10. The small molecule sodium hyaluronate self-assembled structure prepared according to the method described in item 9 is the self-assembled structure described in any one of items 1 to 8.
[0025] 11. Use of the self-assembled structure according to any one of items 1 to 8 or the self-assembled structure prepared by the method according to any one of items 9 to 10 in alleviating the yellowing of small molecule sodium hyaluronate.
[0026] 12. Use of the self-assembled structure according to any one of items 1 to 8 or the self-assembled structure prepared by the method according to any one of items 9 to 10 in skin care products,
[0027] Preferably, the skin care product is lotion, milk, ointment or cream.
[0028] 13. A skin care product comprising the self-assembly structure according to any one of items 1 to 8.
[0029] Effects of the Invention
[0030] 1. The sodium hyaluronate self-assembly structure provided by the present invention can effectively alleviate the phenomenon of small molecule sodium hyaluronate turning yellow at high temperature in aqueous solution.
[0031] 2. The present invention further forms a sodium hyaluronate self-assembly structure by rationally compounding hydrolyzed sodium hyaluronate with acetylated sodium hyaluronate, which can reduce the particle size of the self-assembly structure, thereby better alleviating the yellowing problem of small molecule sodium hyaluronate.
[0032] 3. The sodium hyaluronate self-assembly structure provided by the present invention can be applied to skin care products such as water, lotion, cream, etc. to alleviate the problem of product yellowing caused by small molecule sodium hyaluronate. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the specific implementation of the present invention or the technical solutions in the prior art, the following will briefly introduce the drawings required for the specific implementation or the prior art description. Obviously, the drawings described below are some implementations of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. Among them:
[0034] Figure 1 It is a nanostructure formed by self-assembly of hydrolyzed sodium hyaluronate;
[0035] Figure 2 It is a nanostructure formed by self-assembly of hydrolyzed sodium hyaluronate and acetylated sodium hyaluronate. DETAILED DESCRIPTION
[0036] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] It should be noted that certain words are used in the specification and claims to refer to specific components. Those skilled in the art should understand that technicians may use different nouns to refer to the same component. This specification and claims do not use the difference in nouns as a way to distinguish components, but use the difference in the functions of the components as the criterion for distinction. As mentioned throughout the specification and claims, "including" or "comprising" are open-ended terms and should be interpreted as "including but not limited to". The subsequent description of the specification is a preferred embodiment of the present invention, but the description is based on the general principles of the specification and is not intended to limit the scope of the present invention. The scope of protection of the present invention shall be determined by the attached claims.
[0038] The present invention provides a self-assembly structure containing hydrolyzed sodium hyaluronate.
[0039] The average particle size of the self-assembled structure provided by the present invention is 300-2000nm.
[0040] The average particle size of the present invention refers to the D50 particle size, which is the particle diameter corresponding to the cumulative particle size distribution percentage of the sample reaching 50%, also known as the median diameter or median particle size. The method of measuring the average particle size D50 of the present invention includes but is not limited to using measuring instruments such as a particle size analyzer, a dynamic laser light scattering instrument, a laser particle size analyzer, etc. for measurement.
[0041] In a specific embodiment of the present invention, the average particle size of the present invention is measured using a NanoBrook 90Plus PALS dynamic laser light scattering instrument.
[0042] The average particle size of the self-assembled structure of the present invention is 300-2000nm, for example, the average particle size is 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm, 1000nm, 1100nm, 1200nm, 1300nm, 1400nm, 1500nm, 1600nm, 1700nm, 1800nm, 1900nm, 2000nm.
[0043] The hydrolyzed sodium hyaluronate is a highly active ultra-small molecule sodium hyaluronate, which has a higher transdermal absorption rate than general macromolecular sodium hyaluronate, moisturizes more deeply, increases the moisture content of the skin, and can repair damaged skin and increase cell activity, thereby reducing environmental damage to skin cells. The degree of polymerization of hydrolyzed sodium hyaluronate refers to the number of disaccharide units composed of glucuronic acid and N-acetylglucosamine in the sodium hyaluronate molecule. The molecular weight range can be measured by an Ubbelohde viscometer to obtain the relative viscosity, and the average molecular weight can be calculated according to the formula.
[0044] The self-assembled structure refers to an ordered structure spontaneously formed by basic structural units (molecules, nanomaterials, micrometer or larger scale substances). In the process of self-assembly, the basic structural units spontaneously organize or aggregate into a stable structure with a certain regular geometric appearance under the interaction based on non-covalent bonds. The structure and number of self-assembled components and the solvent have an impact on the structure of the self-assembled aggregate.
[0045] Furthermore, in the self-assembled structure of the hydrolyzed sodium hyaluronate, the degree of polymerization of the hydrolyzed sodium hyaluronate is 2-20.
[0046] The degree of polymerization is an indicator of the size of polymer molecules. It is based on the number of repeating units, that is, the average number of repeating units contained in the polymer macromolecule chain, represented by n.
[0047] As mentioned above, the degree of polymerization of hydrolyzed sodium hyaluronate can be 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20.
[0048] Furthermore, the self-assembled structure of the hydrolyzed sodium hyaluronate is formed by dissolving in an aqueous solution of a polyol.
[0049] Furthermore, the mass ratio of the hydrolyzed sodium hyaluronate to the polyol is 1:1 to 1:30. For example, the mass ratio can be 1:2 to 1:29, 1:3 to 1:28, 1:3 to 1:27, 1:4 to 1:26, 1:4 to 1:25, 1:5 to 1:25, 1:5 to 1:24, 1:5 to 1:23, 1:5 to 1:22, 1:5 to 1:21, 1:5 to 1:20, 1:6 to 1:20, 1:7 to 1:18, 1:8 to 1:17, etc.
[0050] Preferably, the ratio of the hydrolyzed sodium hyaluronate to the polyol is 1:5 to 1:20.
[0051] Further, in the self-assembled structure of hydrolyzed sodium hyaluronate as described above, the polyol is selected from any one or a combination of propanol, isopropanol, propylene glycol, 1,3-propylene glycol, dipropylene glycol, glycerol, diglycerol, butylene glycol, 1,3-butylene glycol, 1,2-butylene glycol, 1,4-butylene glycol, 2,3-butylene glycol, pentanediol, 1,2-pentanediol, 1,5-pentanediol, tert-butyl alcohol, diethylene glycol, triethylene glycol, hexanol, 1,2-hexanediol, 1,6-hexanediol, nonanediol, 1,9-nonanediol, lactitol, octanediol, octanediol, and ethylene glycol.
[0052] In some specific embodiments, the polyol is one or more of butanediol, pentanediol, and propylene glycol.
[0053] Preferably, the polyol is butanediol, pentanediol, or propylene glycol;
[0054] Preferably, the polyol is pentanediol or propylene glycol;
[0055] Preferably, the polyol is butanediol or propylene glycol;
[0056] Preferably, the polyol is butanediol or pentanediol;
[0057] Preferably, the polyol is butanediol;
[0058] Preferably, the polyol is pentanediol.
[0059] In the self-assembled structure of hydrolyzed sodium hyaluronate as described above, when the polyol is a combination of pentanediol and butanediol, the mass ratio of butanediol to pentanediol is 1:10 to 10:1. For example, the mass ratio can be 1:10, 1:9, 1:8, 1:7, 1:6, 1:5, 1:4, 1:3, 1:2, 1:1, 10:1, 9:1, 8:1, 7:1, 6:1, 5:1, 4:1, 3:1, 2:1, or 1:1.
[0060] Preferably, the mass ratio of butanediol to pentanediol is 1:5 to 3:1.
[0061] In certain embodiments of the present invention, the self-assembled structure is composed of hydrolyzed sodium hyaluronate, that is, the self-assembled structure contains only one component, hydrolyzed sodium hyaluronate.
[0062] Furthermore, the hydrolyzed sodium hyaluronate self-assembly structure provided by the present invention also includes acetylated sodium hyaluronate.
[0063] The acetylated sodium hyaluronate is obtained by acetylation of sodium hyaluronate. The introduction of acetyl groups makes sodium hyaluronate both hydrophilic and lipophilic, and can play a role in double moisturizing, repairing the stratum corneum barrier, improving skin elasticity and other biological activities. At the same time, due to its lipophilic properties, acetylated sodium hyaluronate has targeting. The molecular weight range of acetylated sodium hyaluronate can be measured by Ubbelohde viscometer to obtain relative viscosity, and calculated according to the formula.
[0064] Further, the molecular weight range of acetylated sodium hyaluronate in the hydrolyzed sodium hyaluronate self-assembled structure as described above is 20 to 100 kDa. For example, the molecular weight can be 20 to 99 kDa, 20 to 98 kDa, 20 to 95 kDa, 20 to 90 kDa, 20 to 88 kDa, 20 to 85 kDa, 20 to 83 kDa, 20 to 80 kDa, 20 to 78 kDa, 20 to 76 kDa, 20 to 70 kDa, 20 to 65 kDa, 20 to 60 kDa, 20 to 55 kDa, 20 to 50 kDa, 20 to 40 kDa, or 20 to 30 kDa.
[0065] Preferably, the molecular weight of the acetylated sodium hyaluronate is 20 to 50 kDa.
[0066] Furthermore, in the self-assembled structure of hydrolyzed sodium hyaluronate as described above, the mass ratio of hydrolyzed sodium hyaluronate to acetylated sodium hyaluronate is 1:4 to 10:1. For example, the mass ratio can be 1:4, 1:3, 1:2, 1:1, 10:1, 9:1, 8:1, 7:1, 6:1, 5:1, 4:1, 3:1, or 2:1.
[0067] Preferably, the mass ratio of the hydrolyzed sodium hyaluronate to the acetylated sodium hyaluronate is 1:2 to 10:1.
[0068] In certain specific embodiments of the present invention, the self-assembled structure is composed of hydrolyzed sodium hyaluronate and acetylated sodium hyaluronate, that is, the self-assembled structure contains only two components, hydrolyzed sodium hyaluronate and acetylated sodium hyaluronate.
[0069] The present invention further provides a method for preparing a self-assembled structure of hydrolyzed sodium hyaluronate, characterized in that it comprises the following steps:
[0070] Weigh hydrolyzed sodium hyaluronate and polyol according to the mass ratio or weigh hydrolyzed sodium hyaluronate, polyol and acetylated sodium hyaluronate according to the mass ratio;
[0071] Dissolve hydrolyzed sodium hyaluronate and polyol in water to form a mixed solution, or dissolve hydrolyzed sodium hyaluronate in water to form phase A, mix acetylated sodium hyaluronate and diol to form phase B, and mix phase A and phase B to form a mixed solution;
[0072] Stirring the mixed solution until it is completely dissolved;
[0073] The completely dissolved solution is allowed to stand and cool;
[0074] Preferably, the mixed solution is heated before being stirred, and the heating temperature may be 30-60° C., for example, the temperature may be 30° C., 32° C., 35° C., 38° C., 40° C., 43° C., 45° C., 48° C., 50° C., 55° C., 60° C. The heating time is maintained at 25-50 minutes.
[0075] Preferably, the heating temperature is 45° C. and the holding time is 30 minutes.
[0076] Furthermore, the hydrolyzed sodium hyaluronate self-assembly structure prepared by any of the above-mentioned preparation methods is any of the hydrolyzed sodium hyaluronate self-assembly structures provided by the present invention as described above.
[0077] Furthermore, the present invention provides the use of any of the aforementioned hydrolyzed sodium hyaluronate self-assembly structures in alleviating the yellowing of small molecule sodium hyaluronate, including but not limited to yellowing due to improper storage, yellowing due to temperature changes, yellowing due to excessive time, and yellowing due to other factors.
[0078] Furthermore, the present invention provides the use of any of the aforementioned hydrolyzed sodium hyaluronate self-assembled structures in skin care products.
[0079] The application includes, but is not limited to, adding the hydrolyzed sodium hyaluronate self-assembled structure provided by the present invention to skin care products, directly combining it with skin care products, and indirectly combining it with other skin care products.
[0080] The skin care products include but are not limited to lotions, emulsions, ointments, creams, essences, sunscreens, oils, body washes, bath products, eye skin care products, facial masks, facial cleansers, makeup removers, foundations, pressed powders, rouge, body makeup, eyebrow makeup, eyeshadows, eyelid makeup, eye hair makeup, eye makeup removers, lip balms, lip glosses, general color lipsticks, and lip liners.
[0081] Furthermore, the skin care product is a product in the form of lotion, milk, ointment, cream, etc.
[0082] The present invention further provides a skin care product, which comprises any one of the hydrolyzed sodium hyaluronate self-assembly structures described above.
[0083] Beneficial effects:
[0084] 1. The self-assembled structure of hydrolyzed sodium hyaluronate provided by the present invention is a self-assembled structure of supramolecular aggregates in the solution. Compared with the sodium hyaluronate dissolved in the solution, it has stronger thermal stability and effectively alleviates the phenomenon that small molecule sodium hyaluronate turns yellow when encountering elevated temperature in the aqueous solution.
[0085] 2. The present invention further provides a self-assembled structure of hydrolyzed sodium hyaluronate prepared by rationally compounding hydrolyzed sodium hyaluronate with acetylated sodium hyaluronate. The acetylated sodium hyaluronate has a certain lipophilicity while being hydrophilic, which can enhance the amphiphilicity of the system. The self-assembled structure of hydrolyzed sodium hyaluronate formed has a denser nanoparticle structure and a smaller particle size, which can more fully wrap the hyaluronic acid unit and prevent it from being oxidized and yellowing at high temperature, thereby better alleviating the yellowing problem of small molecule sodium hyaluronate.
[0086] 3. The self-assembled structure of hydrolyzed sodium hyaluronate provided by the present invention can be applied to various skin care products such as lotions, emulsions, ointments, creams, essences, etc., thereby alleviating the problem of product yellowing caused by the yellowing of small molecule sodium hyaluronate.
[0087] Example
[0088] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0089] Unless otherwise specified, the materials and reagents used in the following examples can be purchased from commercial sources. The hydrolyzed sodium hyaluronate with a degree of polymerization of 10-15 was purchased from Bloomage Biotechnology Co., Ltd. (trade name: Ximinxiu TM Super active hyaluronic acid, batch number: 19122443), acetylated sodium hyaluronate, molecular weight 20-30 kDa, purchased from Bloomage Biotechnology Co., Ltd. (trade name: Hymagic TM -AcHA, batch number: 20081322); the butanediol used was 1,3-butanediol, and the pentanediol used was 1,2-pentanediol.
[0090] Table 1 Composition table of each embodiment and comparative example
[0091]
[0092] Comparative Example 1
[0093] Accurately weigh 0.5 g of hydrolyzed sodium hyaluronate, add water to 100 g, keep at 45°C for 30 min, and stir until completely dissolved.
[0094] Comparative Example 2
[0095] Accurately weigh 0.5 g of hydrolyzed sodium hyaluronate and 0.17 g of acetylated sodium hyaluronate, add 99.33 g of water, maintain at 45°C for 30 min, and stir until completely dissolved.
[0096] Example 1
[0097] Accurately weigh 0.5 g of hydrolyzed sodium hyaluronate, add 91 g of water to dissolve as phase A, add 0.5 g of acetylated sodium hyaluronate, add 8.0 g of butanediol, and disperse evenly to form phase B. Slowly add phase A to phase B, maintain at 45°C for 30 min, and stir until completely dissolved.
[0098] Example 2
[0099] Accurately weigh 0.5 g of hydrolyzed sodium hyaluronate, add 91 g of water to dissolve as phase A, add 0.5 g of acetylated sodium hyaluronate, add 8.0 g of pentylene glycol, and disperse evenly to form phase B. Slowly add phase A to phase B, keep at 45°C for 30 min, and stir until completely dissolved.
[0100] Example 3
[0101] Accurately weigh 0.5 g of hydrolyzed sodium hyaluronate, add 91 g of water to dissolve as phase A, add 0.5 g of acetylated sodium hyaluronate, 7.0 g of butanediol and 1.0 g of pentanediol, and disperse evenly to form phase B. Slowly add phase A to phase B, keep at 45°C for 30 min, and stir until completely dissolved.
[0102] Example 4
[0103] Accurately weigh 0.5 g of hydrolyzed sodium hyaluronate, add 91 g of water to dissolve as phase A, add 0.5 g of acetylated sodium hyaluronate, 5.0 g of butanediol and 3.0 g of pentanediol, and disperse evenly to form phase B. Slowly add phase A to phase B, keep at 45°C for 30 min, and stir until completely dissolved.
[0104] Example 5
[0105] Accurately weigh 0.5 g of hydrolyzed sodium hyaluronate, add 91 g of water to dissolve as phase A, add 0.5 g of acetylated sodium hyaluronate, 4.0 g of butanediol and 4.0 g of pentanediol, and disperse evenly to form phase B. Slowly add phase A to phase B, keep at 45°C for 30 min, and stir until completely dissolved.
[0106] Example 6
[0107] Accurately weigh 0.5 g of hydrolyzed sodium hyaluronate, add 91 g of water to dissolve as phase A, add 0.5 g of acetylated sodium hyaluronate, 1.0 g of butanediol, and 6.0 g of pentanediol, and disperse evenly to form phase B. Slowly add phase A to phase B, maintain at 45°C for 30 min, and stir until completely dissolved.
[0108] Example 7
[0109] Accurately weigh 0.5 g of hydrolyzed sodium hyaluronate, add 98.2 g of water to dissolve as phase A, add 0.5 g of acetylated sodium hyaluronate, 0.5 g of butanediol, and 0.3 g of pentanediol, and disperse evenly to form phase B. Slowly add phase A to phase B, keep at 45°C for 30 min, and stir until completely dissolved.
[0110] Example 8
[0111] Accurately weigh 0.5 g of hydrolyzed sodium hyaluronate, add 97.4 g of water to dissolve as phase A, add 0.5 g of acetylated sodium hyaluronate, 1.0 g of butanediol and 0.6 g of pentanediol, and disperse evenly to form phase B. Slowly add phase A to phase B, keep at 45°C for 30 min, and stir until completely dissolved.
[0112] Example 9
[0113] Accurately weigh 0.5 g of hydrolyzed sodium hyaluronate, add 89 g of water to dissolve as phase A, add 0.5 g of acetylated sodium hyaluronate, 6.25 g of butanediol, and 3.75 g of pentanediol, and disperse evenly to form phase B. Slowly add phase A to phase B, maintain at 45°C for 30 min, and stir until completely dissolved.
[0114] Example 10
[0115] Accurately weigh 0.5 g of hydrolyzed sodium hyaluronate, add 92.6 g of water to dissolve as phase A, add 0.5 g of acetylated sodium hyaluronate, 4 g of butanediol, and 2.4 g of pentanediol, and disperse evenly to form phase B. Slowly add phase A to phase B, maintain at 45°C for 30 min, and stir until completely dissolved.
[0116] Embodiment 11
[0117] Accurately weigh 0.5 g of hydrolyzed sodium hyaluronate, add 86.5 g of water to dissolve as phase A, add 5.0 g of acetylated sodium hyaluronate, 5.0 g of butanediol, and 3.0 g of pentanediol, and disperse evenly to form phase B. Slowly add phase A to phase B, keep at 45°C for 30 min, and stir until completely dissolved.
[0118] Example 12
[0119] Accurately weigh 0.5 g of hydrolyzed sodium hyaluronate, add 89.5 g of water to dissolve as phase A, add 2.0 g of acetylated sodium hyaluronate, 5.0 g of butanediol, and 3.0 g of pentanediol, and disperse evenly to form phase B. Slowly add phase A to phase B, maintain at 45°C for 30 min, and stir until completely dissolved.
[0120] Example 13
[0121] Accurately weigh 0.5 g of hydrolyzed sodium hyaluronate, add 90.5 g of water to dissolve as phase A, add 1.0 g of acetylated sodium hyaluronate, 5.0 g of butanediol, and 3.0 g of pentanediol, and disperse evenly to form phase B. Slowly add phase A to phase B, keep at 45°C for 30 min, and stir until completely dissolved.
[0122] Embodiment 14
[0123] Accurately weigh 0.5 g of hydrolyzed sodium hyaluronate, add 91.5 g of water to dissolve as phase A, add 5.0 g of butanediol and 3.0 g of pentanediol, mix well to form phase B, slowly add phase A to phase B, keep at 45°C for 30 min, and stir until completely dissolved.
[0124] Embodiment 15
[0125] Accurately weigh 0.5 g of hydrolyzed sodium hyaluronate, add 91.25 g of water to dissolve as phase A, add 0.25 g of acetylated sodium hyaluronate, 5.0 g of butanediol, and 3.0 g of pentanediol, and disperse evenly to form phase B. Slowly add phase A to phase B, maintain at 45°C for 30 min, and stir until completely dissolved.
[0126] Example 16
[0127] Accurately weigh 0.5 g of hydrolyzed sodium hyaluronate, add 91.33 g of water to dissolve as phase A, add 0.17 g of acetylated sodium hyaluronate, 5.0 g of butanediol and 3.0 g of pentanediol, and disperse evenly to form phase B. Slowly add phase A to phase B, keep at 45°C for 30 min, and stir until completely dissolved.
[0128] Embodiment 17
[0129] Accurately weigh 0.5 g of hydrolyzed sodium hyaluronate, add 91.365 g of water to dissolve as phase A, add 0.125 g of acetylated sodium hyaluronate, 5.0 g of butanediol, and 3.0 g of pentanediol, and disperse evenly to form phase B. Slowly add phase A to phase B, maintain at 45°C for 30 min, and stir until completely dissolved.
[0130] Embodiment 18
[0131] Accurately weigh 0.5 g of hydrolyzed sodium hyaluronate, add 91.4 g of water to dissolve as phase A, add 0.1 g of acetylated sodium hyaluronate, 5.0 g of butanediol and 3.0 g of pentanediol, and disperse evenly to form phase B. Slowly add phase A to phase B, keep at 45°C for 30 min, and stir until completely dissolved.
[0132] Embodiment 19
[0133] Accurately weigh 0.5 g of hydrolyzed sodium hyaluronate, add 91.45 g of water to dissolve as phase A, add 0.05 g of acetylated sodium hyaluronate, 5.0 g of butanediol and 3.0 g of pentanediol, and disperse evenly to form phase B. Slowly add phase A to phase B, keep at 45°C for 30 min, and stir until completely dissolved.
[0134] Embodiment 20
[0135] Accurately weigh 0.5 g of hydrolyzed sodium hyaluronate, add 91.48 g of water to dissolve as phase A, add 0.02 g of acetylated sodium hyaluronate, 5.0 g of butanediol and 3.0 g of pentanediol, and disperse evenly to form phase B. Slowly add phase A to phase B, keep at 45°C for 30 min, and stir until completely dissolved.
[0136] Test example
[0137] 1. Color change determination
[0138] The prepared samples were placed in an oven at room temperature and 55°C, respectively, and taken out after 10 days. The samples stored at 55°C were compared with those stored at room temperature to observe the color change. The absorbance of each sample at a wavelength of 435nm was tested using an ultraviolet spectrophotometer. Each sample was tested 3 times and the average value was taken. The greater the absorbance at this wavelength, the more obvious the yellowing of the color. The test results are shown in Table 2.
[0139] Color change degree = (A435 -55℃-A 435 -RT)*1000
[0140] Table 2 Color change degree table of each embodiment and comparative example
[0141]
[0142]
[0143] According to the data in the table, at room temperature, after ten days, the colors of the samples of the embodiments and the comparative examples did not change significantly, but at a high temperature of 55°C, after ten days, the colors of the samples of the embodiments and the comparative examples began to deepen and turn yellow to varying degrees. Among them, in Comparative Example 1, the hydrolyzed sodium hyaluronate alone was dissolved in water, and yellowing was more obvious when placed at high temperature. In Comparative Example 2, the solution formed by simultaneously dissolving acetylated sodium hyaluronate and hydrolyzed sodium hyaluronate in water also turned yellow more obviously. The solution formed by the self-assembled structure of hydrolyzed sodium hyaluronate provided by the present invention, as shown in Examples 1 to 20, has a very obvious alleviating effect on the yellowing of the hydrolyzed sodium hyaluronate solution alone, especially in Examples 4, 5, 9, 13, 15, 16, 17, 18, and 19. After being stored for ten days at room temperature and at a high temperature of 55°C, the colors of the samples showed almost no difference, and no obvious yellowing occurred.
[0144] 2. Particle size characterization
[0145] The average particle size and particle size distribution of the samples of the comparative examples and embodiments were measured using a NanoBrook 90Plus PALS dynamic laser light scattering instrument. The particle size of each sample was measured 3 times and the average value was taken. The test results are shown in Table 3.
[0146] According to the data in the table, the hydrolyzed sodium hyaluronate dissolved in water alone does not form a self-assembled structure at room temperature and at a high temperature of 55°C, and the particle size cannot be measured. However, the self-assembled structure of the hydrolyzed sodium hyaluronate provided by the present invention can be observed as self-assembled particles under a dynamic laser light scattering instrument. After measurement, at room temperature, the example samples of the present invention have formed self-assembled structures of different particle sizes. Under a high temperature of 55°C, the particle size of the self-assembled structure in the samples of each example does not increase significantly, indicating that the self-assembled structure provided by the present invention is very stable under high temperature conditions and is not easily destroyed. From the particle size distribution of the examples, it can be seen that the smaller the particle size of the example samples, the less obvious the yellowing of the color, that is, the better the effect of alleviating the yellowing of the color under high temperature.
[0147] Table 3 Particle size variation of each embodiment and comparative example
[0148]
[0149]
[0150] 3. Microstructure Characterization
[0151] The morphology of the samples obtained in Example 14 and Example 15 was characterized by using a Japanese Hitachi S-4800FE-SEM. The above samples were dropped onto a silicon wafer in appropriate amounts, dried, and then subjected to gold spraying. The morphology was then observed. Figure 1 , Figure 2 As shown. Figure 1 It can be seen that under the preparation conditions of the present invention, hydrolyzed sodium hyaluronate forms a self-assembled structure in the polyol solution, which is different from the sodium hyaluronate solution completely dissolved in water. Figure 2 It can be seen that the self-assembled structure formed by hydrolyzed sodium hyaluronate and acetylated sodium hyaluronate has a smaller and denser particle size, which wraps the hyaluronic acid unit more fully and prevents it from being oxidized and yellowed at high temperatures.
[0152] 4. Application in skin care products
[0153] The hyaluronic acid composition can be applied to skin care products. While exerting the skin care effect, it can alleviate the yellowing phenomenon of small molecule HA. For example, 98.5 g of the composition containing the self-assembly structure obtained in Example 15 is taken, and 0.5 g of the active ingredient ectoine, 0.2 g of trehalose, 0.2 g of allantoin, and 0.3 g of xanthan gum are added to prepare an essence. After the essence is placed at a high temperature of 55° C. for 10 days, there is still no obvious yellowing phenomenon. Table 4 is the formula of the essence containing the sodium hyaluronate combination.
[0154] Table 4 Essence ingredients
[0155] Serial number Element quality 1 Example 15 Composition obtained 98.5g 2 Ekdoin 0.5g 3 Trehalose 0.2g 4 Allantoin 0.2g 5 Xanthan gum 0.3g
Claims
1. A self-assembled structure containing hydrolyzed sodium hyaluronate, characterized in that: The average particle size of the self-assembled structure is 300 to 2000 nm, and the self-assembled structure is formed by dispersing hydrolyzed sodium hyaluronate in an aqueous solution of pentanediol and / or butanediol; The mass ratio of the hydrolyzed sodium hyaluronate to pentanediol and / or butylene glycol is 1:1 to 1:30; The degree of polymerization of the hydrolyzed sodium hyaluronate is 2-20.
2. A self-assembled structure containing hydrolyzed sodium hyaluronate, characterized in that: The average particle size of the self-assembled structure is 300 to 2000 nm, and the self-assembled structure is formed by dispersing hydrolyzed sodium hyaluronate and acetylated sodium hyaluronate in an aqueous solution of pentanediol and / or butylene glycol; The mass ratio of the hydrolyzed sodium hyaluronate to the acetylated sodium hyaluronate is 1:4 to 10:1; The mass ratio of the hydrolyzed sodium hyaluronate to pentanediol and / or butylene glycol is 1:1 to 1:30; The degree of polymerization of the hydrolyzed sodium hyaluronate is 2 to 20; The molecular weight of the acetylated sodium hyaluronate is 20 to 100 kDa.
3. The self-assembled structure according to claim 1 or 2, characterized in that: The mass ratio of the hydrolyzed sodium hyaluronate to pentanediol and / or butylene glycol is 1:5 to 1:
20.
4. The self-assembled structure according to claim 1 or 2, characterized in that: The polyol is a combination of pentanediol and butanediol, and the mass ratio of butanediol to pentanediol is 1:10 to 10:
1.
5. The self-assembled structure according to claim 4, characterized in that: The mass ratio of butanediol to pentanediol is 1:5 to 3:
1.
6. The self-assembled structure according to claim 1, characterized in that: The self-assembled structure consists of hydrolyzed sodium hyaluronate.
7. The self-assembled structure according to claim 2, characterized in that: The molecular weight of the acetylated sodium hyaluronate is 20 to 50 kDa.
8. The self-assembled structure according to claim 2, characterized in that: The mass ratio of the hydrolyzed sodium hyaluronate to the acetylated sodium hyaluronate is 1:2 to 10:
1.
9. The self-assembled structure according to claim 2, characterized in that: The self-assembly structure consists of hydrolyzed sodium hyaluronate and acetylated sodium hyaluronate.
10. A method for preparing the self-assembled structure of hydrolyzed sodium hyaluronate according to any one of claims 1 to 9, characterized in that: The steps include: Weigh hydrolyzed sodium hyaluronate, pentylene glycol and / or butylene glycol according to the mass ratio, or weigh hydrolyzed sodium hyaluronate, pentylene glycol and / or butylene glycol, and acetylated sodium hyaluronate according to the mass ratio; Dissolve hydrolyzed sodium hyaluronate, pentylene glycol and / or butylene glycol in water to form a mixed solution, or dissolve hydrolyzed sodium hyaluronate in water to form phase A, mix acetylated sodium hyaluronate with pentylene glycol and / or butylene glycol to form phase B, and mix phase A and phase B to form a mixed solution; Stirring the mixed solution until it is completely dissolved; The completely dissolved solution was allowed to stand and cool.
11. The method according to claim 10, characterized in that The mixed solution is heated before being stirred.
12. The method according to claim 11, characterized in that The heating temperature is 30-60° C., and the holding time is 25-50 minutes.
13. The small molecule sodium hyaluronate self-assembled structure prepared according to the method according to any one of claims 10 to 12 is the self-assembled structure according to any one of claims 1 to 9.
14. Use of the self-assembled structure according to any one of claims 1 to 9 or the self-assembled structure prepared by the method according to any one of claims 10 to 12 in alleviating the yellowing of small molecule sodium hyaluronate.
15. Use of the self-assembled structure according to any one of claims 1 to 9 or the self-assembled structure prepared by the method according to any one of claims 10 to 12 in skin care products.
16. The use according to claim 15, wherein the skin care product is lotion, milk, ointment or cream.
17. A skin care product comprising the self-assembled structure according to any one of claims 1 to 9.
Citation Information
Patent Citations
A hyaluronic acid-astaxanthin self-assembled nano system and the preparation method and its application
AU2021106295A4
Preparation method of in-situ induced hyaluronic acid micelle
CN102718976A